Tapping into science and genetic literacy: Exploring gender-based disparities in a malang district high school - Ladysyah Fitri Rohmah; Iin Hindun; Husamah Husamah; Diani Fatmawati; Ahmad Fauzi (Biosfer: Jurnal Pendidikan Biologi, 2023)
The influence of gender on science and genetic literacy emerges as a compelling issue within the realm of scientific education, prompting an exploration within the confines of a high school located in the Malang district. This quantitative investigation is designed to ascertain the gender-based influence on both science literacy and genetic literacy among students at a Senior High School within the Malang District. The study encompasses three distinct clusters of participants: the first cluster comprises 12 male students and 22 female students from the first-grade level, the second cluster consists of 9 male students and 22 female students from the second-grade level, and the final cluster comprises 10 male students and 19 female students from the third-grade level, amounting to a total of 94 students. The administration of science literacy and genetic literacy instruments was conducted through Google Forms, allowing the researchers to collect the necessary data. Subsequently, the accumulated data will undergo rigorous analytical scrutiny employing the One-Way ANOVA test. The outcomes of the analysis revealed a lack of statistically significant disparity in science literacy across genders [F(1.92)=0.102, p=0.750], as well as a non-significant difference in genetic literacy attributed to gender variations [F(1.92) =0.773, p=0.382]. In light of these findings, the implications for educational policies and interventions are discussed to enhance pedagogical practices and learning outcomes for both male and female students.